Proteomic analysis of the spineless cuttlefish Sepiella japonica: Exploratory analyses on the phenomenon of death after spawning - Li, Hongfei; Lin, Shuangrui; Qi, Pengzhi; Wang, Jingtian; Fan, Meihua; Huang, Hongwei; Dong, Zhenyu; Xu, Kaida; Guo, Baoying (Frontiers in Marine Science, 2022)
To better understand the physiological events involving death after spawning in S. japonica (Japanese spineless cuttlefish), we have presently generated a proteomic data set to properly examine this phenomenon. As such, a proteomic-based approach was employed to identify differentially expressed proteins (DEPs) in the optic glands of S. japonica, at three distinct growth stages: pre-spawning after sexual maturity (group A); spawning (group B) and postspawning before death (group C). About 955, 1000, and 1024 DEPs were identified for each comparative group analysis (i.e., group B vs A, group B vs C, and group C vs A). We further discovered that the function of these newly identified DEPs was mostly related to molecular events such as gene translation and signal transduction. According to the enriched GO terms obtained by Gene Ontology analysis, the function of most DEPs was correlated with structural molecule activity, ribosome function and gene expression. The majority of DEPs were known to be involved in signal transduction and energy metabolism, interestingly, some aging-related DEPs were also identified. Putting together, our study provides new insights, at the protein level, in the phenomenon of death after spawning in S. japonica, by referring to anti-aging effects conserved in other cephalopoda species.